2017
DOI: 10.1021/jacs.7b03381
|View full text |Cite
|
Sign up to set email alerts
|

On-Surface Synthesis of Sandwich Molecular Nanowires on Graphene

Abstract: We demonstrate a new synthesis route for the growth of organometallic sandwich molecular nanowires, taking the example of Eu-cyclooctatetraene (EuCot), a predicted ferromagnetic semiconductor. We employ simultaneous exposure of Cot molecules and Eu vapor in ultrahigh vacuum to an inert substrate, such as graphene. Using a Cot excess under temperature conditions of a finite residence time of the molecule, the reactand diffusion confined to two dimensions results in a clean product of ultralong wires. In situ sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 65 publications
2
36
0
Order By: Relevance
“…In DFT calcuations naphthalene is used as a paradigm for an aromatic molecule to explore the anisotropic energy landscape of physisorption induced by the wave pattern. Based on these insights, unaxial alignment of sandwich-molecular wires during organometallic on-surface synthesis [8,38] is experimentally demonstrated. Inert single-crystal substrates are rare, but attractive for the growth of quasifreestanding 2D layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation

Single-crystal graphene on Ir(110)

Kraus,
Huttmann,
Fischer
et al. 2021
Preprint
Self Cite
“…In DFT calcuations naphthalene is used as a paradigm for an aromatic molecule to explore the anisotropic energy landscape of physisorption induced by the wave pattern. Based on these insights, unaxial alignment of sandwich-molecular wires during organometallic on-surface synthesis [8,38] is experimentally demonstrated. Inert single-crystal substrates are rare, but attractive for the growth of quasifreestanding 2D layers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its inertness, Gr is also well suited as substrate when investigating the properties of molecular layers in the absence of strong molecule-substrate hybridization [6,7]. Similarly, its inertness makes it an ideal substrate for organometallic chemistry with the function to confine the reactand diffusion to two dimensions [8]. In case of Gr forming a moiré with its growth substrate, also templating of molecular layers [9] and of atom or cluster superlattices has been reported [10,11].…”
Section: Introductionmentioning
confidence: 99%

Single-crystal graphene on Ir(110)

Kraus,
Huttmann,
Fischer
et al. 2021
Preprint
Self Cite
“…Pure organic 1D materials can be obtained through catalyzed C−C coupling reactions on surface from halogenated precursors [7, 8] . Alternatively, 1D coordination‐polymers (CPs) can be isolated through coordination chemistry, the covalent bond formation resulting from on‐surface reactions between metal atoms and suitable linker groups [9–14] . One major advantage of this approach is the possibility to tune the properties of the wires by changing the nature of the metal and/or the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Alternatively,1 D coordination-polymers (CPs) can be isolated through coordination chemistry,the covalent bond formation resulting from on-surface reactions between metal atoms and suitable linker groups. [9][10][11][12][13][14] One major advantage of this approach is the possibility to tune the properties of the wires by changing the nature of the metal and/or the ligand. In this strategy,t he ligand design is crucial since maximizing the conjugation through coordination requires keeping the p-d systems as coplanar as possible.Previous studies reported that low-lying p*o rbitals of quinoidal ligands can mix extensively with the valence d-orbitals of am etal center, yielding complexes in which the electrons could be delocalized over both the metal and the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[1−4] Besides, metallocenes play an important role in the development of new class of materials, associated with intriguing electronic and magnetic properties Recently a new surface−supported one−dimensional organometallic sandwich molecular nanowires associated with ferromagnetic insulator properties has been synthesized . Discovery of the first sandwich complex, viz., biscyclopentadienyl Iron [Fe(C 5 H 5 ) 2 ] (ferrocene) has provided an extensive series of breakthroughs in the field of organometallic chemistry …”
Section: Introductionmentioning
confidence: 99%